LAND POTENTIAL FOR AGRICULTURE IN SUKOSARI VILLAGE, BANDONGAN DISTRICT, MAGELANG, CENTRAL JAVA - Tri Suwarni Wahyudiningsih; Erry Purnomo; Ayu Lestiyani (Universitas Tidar, 2021)
The purpose of this study is to characterize the physical, chemical, and biological properties of Sukosari land. The research was conducted via survey, evaluating the soil properties in agricultural areas to obtain 12 points at various altitudes. The results indicated that sand made up the most significant percentage of texture, ranging from 56 to 67 %. The analysis results of the soil's degree of acidity (pH) indicate that it is acidic, ranging between 4-5. The analysis of soil organic carbon, nitrogen, phosphorus, and potassium yielded low values. The total number of bacteria and fungi in the soil, on the other hand, is relatively high. As a result, it can be concluded that Sukosari's soil fertility is still relatively low. Additionally, it is recommended that the microorganisms present in each type of soil and land use Sukosari are identified.